2021
DOI: 10.12659/msm.933027
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Continuous and Noninvasive Hemoglobin Monitoring in the Presence of CO2 Insufflation: An Observational Pilot Study

Abstract: Background Laparoscopic surgery has several benefits, but it requires prolonged carbon dioxide (CO 2 ) insufflation. Several factors affect the accuracy of continuous and noninvasive hemoglobin (SpHb) monitoring, but the effects of CO 2 insufflation are undetermined. This study investigated the effect of CO 2 insufflation on SpHb monitoring in laparoscopic surgery. Material/Methods Twenty p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Pulse oximetry and pulse CO-Oximetry have technological similarity based on light absorption through a finger sensor. Recently, an observational pilot study suggested that the values of SpHb may be affected by the presence of CO 2 insufflation [14]. Therefore, we hypothesized that increased end-tidal CO 2 (EtCO 2 ) would affect sensing of SpHb and reduce the accuracy and trending ability of SpHb during laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse oximetry and pulse CO-Oximetry have technological similarity based on light absorption through a finger sensor. Recently, an observational pilot study suggested that the values of SpHb may be affected by the presence of CO 2 insufflation [14]. Therefore, we hypothesized that increased end-tidal CO 2 (EtCO 2 ) would affect sensing of SpHb and reduce the accuracy and trending ability of SpHb during laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%